Politicians, Bureaucrats and Leadership in Organizations - Burnham, J. author. aut Link
XI, 261 p.
Keywords: This is the first book in English on the French agency DATAR-DIACT that has been the envy of regional planners worldwide. It sheds new light on political leadership in a bureaucracy and demonstrates convincingly the impact of political leaders on institutions. It is a study of France with lessons for other political and administrative systems.